A novel method for gear crack fault diagnosis using improved analytical-FE and strain measurement. (15th October 2020) - Wu, Jiateng; Yang, Yu; Wang, Ping; Wang, Jian; Cheng, Junsheng
Highlights: A novel method avoids drawback of AM for cracked gear, keeping higher accuracy. The strain measurement technique is introduced to obtain practical TVMS. The model parameter can be inversely reflected by using strain signal. The effect of crack depth on vibration feature of the gear system is reflected. Abstract: In this paper, a novel analytical-FE method which overcomes the drawbacks of the analytical method (AM) and finite element method (FEM) is proposed to evaluate time-varying meshing stiffness (TVMS) under the different gear crack status. In this method, the strain measurement technique is introduced. As a modern measurement technique, the proposed method can provide the strain signal of the cracked gear which can be used to modify the FE model parameter to obtain the engineering practical TVMS. In addition, it provides a new research idea that the model parameter can be inversely reflected by using engineering practical signal. The analysis result of dynamic response show that the proposed method can reflect the effect of various crack depths on the vibration features of the gear system, and the validity of the proposed method is verified by the vibration signal analysis of experimental rig.